Effects of Nd3+ Donor Doping on Dielectric, Electrical Conductivity and Ferroelectric Properties of (Bi0.5Na0.5)0.93Ba0.07TiO3 Lead-Free Ceramics. Issue 1 (29th December 2021) - Premwichit, Pathit; Kosasang, Onthida; Triamnak, Narit; Prasertpalichat, Sasipohn
Abstract: In this study, lead-free (Bi0.465 Na0.465 Ba0.07 )1− x Nd x TiO3 ( x  = 0.00, 0.01, 0.02 and 0.03) piezoceramics were prepared via conventional solid state mixed-oxide route. The role of A-site Nd 3+ donor doping was investigated through systematic studies of crystal structure, morphology, dielectric, electrical conductivity and ferroelectric properties. The X-ray diffraction data revealed single-phase perovskite structure with pseudocubic symmetry for all samples. The morphology exhibited dense microstructure with the average grain size that tended to decrease with increasing x . Compared to undoped BNBT ( x  = 0), the dielectric loss (tan δ ) at high temperature (> 350 °C) significantly decreased with increasing Nd 3+ doping level. With increasing x, the impedance spectroscopy data revealed more electrically homogeneous microstructure with a significant increase in resistivity ( ρ ) from 3.98 × 10 4 Ω.m (BNBT) to 4.83 × 10 5 Ω.m at x  = 0.02. In addition, Nd 3+ doping can induce a transition from a square-like to a slant P-E hysteresis loop with a significant drop in coercive field ( E c ) (from 25.81 for BNBT to 8.48 kV/cm for x  = 0.03) and remanent polarization ( P r ) (from 27.93 to 3.67 µC/cm 2 ), corresponding to the ergodic relaxor. These results suggest A-site Nd 3+ doped 0.93BNT-0.07 ceramic as a promising candidate for high temperature capacitors and actuator materials.